LANGUAGE USE BETWEEN MALE AND FEMALE HOST IN HITAM PUTIH TALK SHOW - Nurmaliana Sari; Sumarsih Sumarsih; Busmin Gurning (LINGUISTIK TERAPAN, 2019)
This study discusses about language use occurred by male and female host in Hitam Putih talk show. The research is conducted by applying qualitative descriptive design. The subjects of this study are male and female host in Hitam Putih talk show. The data are the utterances produced by male and female host in Hitam Putih talk show. This research focuses on the show broadcasted on October 2016 by taking 4 videos randomly. The objectives of this study are (1) to describe kinds of the language use uttered by male and female host in Hitam Putih talk show, (2) to elucidate language use represented by male and female host in Hitam Putih talk show and (3) to describe reasons of different language use by male and female host in Hitam Putih talk show in the ways they are. Additionally, the data are analyzed by applying theory of Interactive Model. The findings showed that the kinds of language use consist of 6 parts such as specialized vocabulary, expletives, empty adjectives, tag questions, polite form and telling joke or humor. The dominant language use uttered by male host is expletive, because male’s utterances are frequently stated in a negative connotation. There are common expressions generally referring to English expletives such as: bad language, profanity, swearwords, cursing, foul language, etc. On the other hand, female host utterances are found in specialized vocabulary as the most dominant because female host has more interest in talking family affairs, such as the education of children, clothes, cooking, and fashion, etc. Women also tended to talk about one thing related to the home and domestic activities. However, the representation of language use uttered by male and female are deficit, dominance and different. And the reason of this matter because of some factors such as psychology and different social status.Key words: Language use, Gender, Talk show